Simple Solutions for Complex Problems: Rethinking Support for Adolescent Mental Health in Soweto, South Africa. - Madonsela, Sonto Gugu; Scott, Megan; Watermeyer, Jennifer; Ware, Lisa Jayne; Niroumand Sarvandani, Mohammad (Health & Social Care in the Community, 2026)
Background: Mental health challenges are among the most critical health issues facing young people in low‐ and middle‐income countries, but with limited resources. Nearly half of adult mental health conditions begin by age 14, making adolescence a critical period for mental health promotion and intervention. Mobile mental health (M‐mHealth) interventions have been promoted as sustainable and scalable in terms of reach and impact. Research on adolescents′ use of M‐mHealth, particularly in high‐income countries, shows the effectiveness of mHealth interventions in reducing symptoms of anxiety, depression and stress. However, adolescents in LMICs face unique challenges, such as internet access and data costs, smartphone prices and a lack of privacy in the home, among others, which may hinder their successful implementation and use in this region. Aim: To identify the key priorities for adolescents in these settings for mental health interventions that are sustainable, contextually tailored and have the potential to promote adolescent well‐being. Methods: This study used a participatory visual methodology (PVM) through workshops. Participants were recruited in Soweto via snowball sampling. Seven PVM workshops were conducted with adolescents (13–18). The data were analysed using inductive thematic analysis. Results: The findings indicate that M‐mHealth interventions may potentially address mental healthcare needs and services. However, currently, this approach may not be the most suitable solution for adolescents in this context. Instead, it is important to create safe communities with basic amenities, strengthen caregiver–adolescent relationships and enhance peer support. Conclusion: Before considering more complex solutions like M‐mHealth interventions, it is important to ensure that adolescents' material needs are provided for, along with having supportive caregivers.